Consumer behaviour : a European perspective - Solomon, Michael R., 1956-; Askegaard, Søren, 1961-; Bamossy, Gary J., 1949- (Harlow : Pearson, 2016)
Now in its sixth edition, Consumer Behaviour: A European Perspective provides a fully comprehensive, lively and engaging introduction to the behaviour of consumers in Europe and around the world. This text offers a cutting-edge overview of consumer behaviour and is ideal for second and third year undergraduates as well as master's students.
Revised edition of Consumer behaviour, 2013.
Keywords: Consumer behavior -- Europe